The "Temporary Recommendations for Use": A dual-purpose regulatory framework for off-label drug use in France. Issue 11 (November 2015) - Degrassat-Théas, Albane; Bocquet, François; Sinègre, Martine; Peigné, Jérôme; Paubel, Pascal
Highlights: Temporary Recommendations for Use (RTUs) have been implemented in France in 2012. RTUs aim to control off-label drug use by establishing patient monitoring and collecting data. The outcome should be an extension the Marketing Authorization (MA). The need to bypass the MA appeared for economic reasons and not only for clinical purposes. Three years later, both legal and technical issues remain. Abstract: In 2012, following the Mediator ® (benfluorex) scandal, France displayed the ambitious goal to implement a regulatory framework for controlling off-label drug use: the "Temporary Recommendations for Use" (RTUs). It aims to regulate the use of pharmaceuticals outside the scope of a marketing authorization (MA) by establishing a framework for patient monitoring and data collection. This is intended to ensure that the benefit/risk ratio is favorable for the indication approved by the RTU. The granting of an RTU enables the reimbursement of off-label drug use and encourages pharmaceutical companies to expand their MA. Between 2012 and 2014, the regulator framework for RTUs was amended twice in order to allow the bypassing of an MA for economic reasons, when a licensed alternative drug exists (so far, this is only illustrated by the bevacizumab (Avastin ® )/ranibizumab (Lucentis ® ) case). The primary purpose of the RTU framework is interesting by implementing an original national control for off-label uses that respond to a public health need. The secondary purpose is more controversial as it promotes off-label use. This has raised legal issues and has created a ground for litigation between pharmaceutical firms and health authorities. RTUs provide an interesting example for other countries that are exploring the possibility of regulating off-label drug use. At the same time, the processes surrounding the implementation of RTUs illustrate the difficulties of public policies to balance public health needs, safety and economic goals.